(untitled) (Journal of the College of Basic Education, 2022)
The importance of the mark is evident in its being a means of introductory visual communication that aims to convey a specific idea to the public so that the idea has a clear and understandable meaning according to creative aesthetic formulas in a contemporary global language, which is a visual design language, in addition to being the link between the institution that stands behind The product and the audience of the recipients, so this study seeks to investigate the mechanism of integration of the design structure system of the trademark, in order to reach the semantic understanding and interpretation of the visual text of these signs.